Development of a universal influenza a vaccine based on virus-like particles of Macrobrachium rosenbergii nodavirus - Ong, Hui Kian (2018)
Influenza A virus (IAV) claims approximately 290,000 to 650,000 lives annually across the globe. Current influenza vaccines are composed of haemagglutinin (HA) and neuraminidase (NA) of the IAV and were shown to be effective in inducing strong and long-lasting HA and NA specific immunities. However, annual reformulation of the seasonal influenza vaccine is required to catch up the rapid mutations of HA and NA. Effectiveness of a seasonal influenza vaccine could vary considerably from 60 to 90% depending on the similarities of HA and NA proteins of the circulating strains and that of the vaccine strains. Seasonal influenza vaccine effectiveness could be as low as 10% in the case of incorrect prediction of IAV mutations. Therefore, a universal influenza vaccine is in urgent need. Extracellular domain of matrix 2 protein (M2e) of IAV represents a potential candidate for the development of a universal influenza vaccine due to its highly conserved amino acid sequence among IAVs. Nevertheless, M2e is poorly immunogenic in nature and requires a larger carrier to enhance its immunogenicity. Multiple copies of M2e epitopes were previously fused to the C-terminal end of Macrobrachium rosenbergii nodavirus capsid protein (NvC), producing a chimeric protein with three copies of M2e (NvC-M2ex3) which self-assemblies into virus-like particles (VLPs). Although NvC-M2ex3 was demonstrated to be immunogenic in the presence of adjuvants, its protective efficacy has not been investigated in vivo. Therefore, as a continuation of the previous study, induced immune responses, protective efficacy and universality of NvC-M2ex3 against influenza A virus infections were elucidated in this project. BALB/c mice immunised subcutaneously with NvC-M2ex3 were shown to elicit strong M2e specific humoral immune responses even in the absence of adjuvant. When challenged with lethal mouse-adapted H1N1 or H3N2, NvC-M2ex3 immunised mice exhibited 100% survival with reduced morbidity and weight loss in addition to the reduced viral load and viral shedding compared to the control groups. In the histopathological aspect, NvC-M2ex3 immunised mice also experienced mitigated immunopathology in lungs upon influenza A infections. Cytokine responses of the mice immunised with NvC-M2ex3 were found to be different when challenged with different influenza A viruses. A higher level of IFN-γ and IL-12 but no significant difference of IL-6 was detected in the lungs of the NvC-M2ex3 immunised mice compared to the control group upon H1N1 infection. Contrarily, when challenged with H3N2, they exhibited lower level of IFN-γ and IL-6 although a higher level of IL-12 was observed in the lungs. Collectively, this study demonstrated the protective efficacy of NvC-M2ex3 against lethal H1N1 and H3N2 infections.